2010
DOI: 10.1080/08927014.2010.511200
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antibiofilm activity of a coral associated actinomycete against drug resistant Staphylococcus aureus biofilms

Abstract: Staphylococcus aureus is now amongst the most important pathogenic bacteria responsible for bloodstream nosocomial infections and for biofilm formation on indwelling medical devices. Its increasing resistance to common antibiotics, partly attributed to its ability to form biofilms, is a challenge for the development of new antimicrobial agents. Accordingly, the goal of this study was to evaluate the effect of a coral associated actinomycete (CAA)-3 on S. aureus biofilms both in vitro and in vivo. Methanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 33 publications
5
57
0
1
Order By: Relevance
“…Apart from antimicrobials, coral associated bacteria including actinomycetes have been reported to produce quorum sensing inhibitors and antibiofilm compounds against the notorious human pathogen Streptococcus pyogenes (Thenmozhi et al 2009;Nithyanand et al 2010). As the incidence of drug resistant bacteria and its virulence mechanisms are on the rise, coral associated bacteria might be targeted for novel pharmaceutical and anti virulent compounds as it has recently been shown that coral associated actinomycetes efficiently inhibited the biofilms of methicillin resistant Staphylococcus aureus (MRSA) both in vitro and in vivo using the nematode Caenorhabditis elegans (Bakkiyaraj and Pandian 2010). Apart from this, coral associated microbial communities play a symbiotic role by defending the coral holobiont against pathogens and assimilating nutrients from the surrounding ecosystem to the coral holobiont.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from antimicrobials, coral associated bacteria including actinomycetes have been reported to produce quorum sensing inhibitors and antibiofilm compounds against the notorious human pathogen Streptococcus pyogenes (Thenmozhi et al 2009;Nithyanand et al 2010). As the incidence of drug resistant bacteria and its virulence mechanisms are on the rise, coral associated bacteria might be targeted for novel pharmaceutical and anti virulent compounds as it has recently been shown that coral associated actinomycetes efficiently inhibited the biofilms of methicillin resistant Staphylococcus aureus (MRSA) both in vitro and in vivo using the nematode Caenorhabditis elegans (Bakkiyaraj and Pandian 2010). Apart from this, coral associated microbial communities play a symbiotic role by defending the coral holobiont against pathogens and assimilating nutrients from the surrounding ecosystem to the coral holobiont.…”
Section: Discussionmentioning
confidence: 99%
“…As examples, an extract from Streptomyces albus inhibited biofilm formation of Vibrio harveyi (You et al 2007), and methanol extracts of coral-associated S. akiyoshiensis inhibited biofilm formation of S. aureus (Bakkiyaraj and Pandian 2010). However, no further information on these anti-biofilm compounds and their mechanisms of biofilm reduction has been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Biofilm inhibitory concentration (BIC)-lowest concentration required to inhibit the biofilm formation-of the extracts was assessed against P. aeruginosa PAO1 with varying concentrations (5-2,500 lg mL -1 ) and found to be 1.75 mg mL -1 . Further, the activity of CAB extracts on the growth of P. aeruginosa PAO1 was studied and found no significant reduction in growth of CAB treated cultures which further prove the potential of CAB extracts as a candidate for QSI.Inhibition of biofilm formation by the CAB extracts was studied as earlier [11]. Both the light microscopic and confocal images have shown the reduction in surface area covered by the biofilms in slides treated with extracts (Fig.…”
mentioning
confidence: 99%
“…Inhibition of biofilm formation by the CAB extracts was studied as earlier [11]. Both the light microscopic and confocal images have shown the reduction in surface area covered by the biofilms in slides treated with extracts (Fig.…”
mentioning
confidence: 99%